2018
DOI: 10.1002/ejic.201701416
|View full text |Cite
|
Sign up to set email alerts
|

An Unsymmetric Ligand with a N5O2 Donor Set and Its Corresponding Dizinc Complex: A Structural and Functional Phosphoesterase Model

Abstract: To mimic the active sites of the hydrolytic enzyme zinc phosphotriesterase, a new dinucleating unsymmetric ligand,amino}acetic acid), has been synthesized and characterized. The hydrolytic efficacy of the complex solution (PICIMP/ZnCl 2 = 1:2) has been investigated using bis-(2,4-dinitrophenyl)phosphate (BDNPP), a DNA analogue substrate. Speciation studies were undertaken by potentiometric titrations at varying pH for both the ligand and the corresponding dizinc complex to elucidate the formation of the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…IR characterization of 2 shows characteristic asymmetric (ν asym ) and symmetric (ν sym ) C = O stretching bands as a broad peak at 1,614 cm −1 and two very sharp peaks for ν sym at 1,490 and 1,453 cm −1 , consistent with the presence of two bridging formates (Deacon and Phillips, 1980; Kurtz, 1990; Das et al, 2014a,b, 2018). In addition, the presence of a very sharp band at 1,080 cm −1 confirms the presence of perchlorate anions; the bands at 744 and 620 cm −1 correspond to the asymmetric and symmetric stretching modes of the Fe-O-Fe units (Kurtz, 1990; Norman et al, 1990).…”
Section: Resultsmentioning
confidence: 89%
“…IR characterization of 2 shows characteristic asymmetric (ν asym ) and symmetric (ν sym ) C = O stretching bands as a broad peak at 1,614 cm −1 and two very sharp peaks for ν sym at 1,490 and 1,453 cm −1 , consistent with the presence of two bridging formates (Deacon and Phillips, 1980; Kurtz, 1990; Das et al, 2014a,b, 2018). In addition, the presence of a very sharp band at 1,080 cm −1 confirms the presence of perchlorate anions; the bands at 744 and 620 cm −1 correspond to the asymmetric and symmetric stretching modes of the Fe-O-Fe units (Kurtz, 1990; Norman et al, 1990).…”
Section: Resultsmentioning
confidence: 89%
“…Das et al carried out DFT calculations on the hydrolysis of BDNPP by the unsymmetric dinuclear Zn(II) complex [Zn 2 L3 (μ-OH)] + (Figure 7) which indicated that in the first step the phosphodiester binds to Zn1 in the N 3 O 2 site followed by a concerted step with a transition state in which μ-OH is shifted toward Zn1 and the substrate adopts a bridging coordination mode (Das et al, 2014). DFT studies on the dizinc(II) complex of an analogous N 5 O 2 ligand containing two 1-methylimidazole moieties (Das et al, 2018) and on the related unsymmetric dizinc(II) complex [Zn 2 L4 (μ-OH)(OH)] found the same mechanism (Daver et al, 2016). By contrast, DFT calculations of the hydrolysis of BNPP by trans -[Zn 2 ( L1 a )(H 2 O)(OH)] + suggested a stepwise mechanism involving nucleophilic attack by a terminally Zn-bound hydroxide and formation of the phosphorane intermediate as the rate-determining step (Zhang et al, 2014b).…”
Section: Phosphodiester Hydrolysismentioning
confidence: 91%
“…Based on kinetic data, X-ray analysis of the complex cocrystallized with a phosphodiester and binding studies, the following mechanisms have been assigned to dinuclear zinc(II) catalysts; (i) monodentate coordination of the phosphodiester to one Zn(II) and nucleophilic attack by OH bound to the other Zn(II) (Bazzicalupi et al, 2004; Jarenmark et al, 2010; Pathak et al, 2018) or to the same Zn(II) (Massoud et al, 2016); (ii) nucleophilic attack by Zn-OH on the bridging substrate (Bazzicalupi et al, 1997, 2004; Daumann et al, 2012, 2013; Brown et al, 2016) and (iii) nucleophilic attack of the bridging substrate by a bridging hydroxide (Das et al, 2014, 2018; Montagner et al, 2014; Daver et al, 2016). As discussed above, a shift of μ-OH to a terminal position in mechanism (iii) would render the attacking hydroxide a better nucleophile.…”
Section: Phosphodiester Hydrolysismentioning
confidence: 99%
“…Compared with extensively studied homogeneous catalysts that hydrolyse diverse phosphoester bonds, [28, 32–50] far fewer heterogeneous systems that catalyse the cleavage of such bonds have been developed. Aiming to stimulate progress in this field, we summarise herein advances in the field of heterogeneous catalysts containing metal ions for organophosphate ester degradation by describing the properties of relevant examples.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30] The use of biomimetic compounds offers a number of advantages, including the possibility to immobilise these compounds on the surface of insoluble solid matrices for easier handling and reuse. [31] Compared with extensivelys tudied homogeneousc atalysts that hydrolyse diverse phosphoester bonds, [28,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] far fewer heterogeneous systemst hat catalyse the cleavage of such bonds have been developed. Aimingt os timulate progress in this field, we summarise herein advances in the field of heterogeneous catalysts containing metal ions for organophosphate ester degradation by describing the properties of relevant examples.…”
Section: Introductionmentioning
confidence: 99%